SUCCESSIVE SALES: CORDIALITY DOES NOT GIVE YOU LOCUS STANDI Cordiant Trading CC v Daimler Chrysler Financial Services (Pty) Ltd 2005 4 SA 389 (D&CLD) - PJ Badenhorst; L Ristow (Obiter, 2022)
Under normal circumstances, the seller is the owner of the merx and ownership is transferred to the purchaser on transfer of possession. However, the seller does not undertake to make the purchaser the owner. His obligation is to deliver the merx, and guarantee the purchaser free and undisturbed possession, that is, to protect the buyer in his possession from eviction. Eviction means any lawful interference with this free and undisturbed possession (vacua possessio), whether by the seller himself or by a third party. The warranty against eviction is in effect a promise by the seller that he will compensate the purchaser if the purchaser is evicted. Constitutum possessorium, as a mode of delivery of ownership of movables, plays an important role in financial arrangements in the motor trade industry. A motor dealer may, for example, arrange with a credit institution that the motor vehicles on its floor, purchased from a manufacturer, be sold to the credit institution and then be resold to the motor dealer. Ownership is transferred to the credit institution by constitutum possessorium. The arrangement between the motor dealer and the credit institution is referred to in the trade as a floor plan agreement.